(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
This study aims to analyze the impact of corruption on foreign direct investment inflows in a sample of ten Arab countries over the period (2013–2021), considering differences across income levels. Panel data techniques were employed, and three econometric models were estimated: the first for all countries, the second for high-income countries, and the third for middle-income countries. The results revealed a statistically significant negative relationship between corruption and indirect foreign investment across all models, supporting the "Sand-the-Wheel" hypothesis. The findings also showed that the impact of corruption was greater in high-income countries than in middle-income countries. The study highlights the importance of enhancing transparency and improving the investment climate in Arab countries.